Metabolic engineering of Paracoccus denitrificans for dual degradation of sulfamethoxazole and ammonia nitrogen - Shenghu Zhou; Rongrong Zhu; Xiaoqian Niu; Yunying Zhao; Yu Deng (Microbiology Spectrum, 2023)
ABSTRACT Sulfamethoxazole (SMX), as one of the most widely used sulfonamide antibiotics, has been frequently detected in the aqueous environment, posing potential risks to the environment and human health. Although microbial degradation methods have been widely applied, some issues remain, including low degradation efficiency and poor environmental adaptability. In this regard, constructing efficient degrading bacteria by metabolic engineering is an ideal solution to these challenges. In this study, we used Paracoccus denitrificans DYTN-1, a superior nitrogen removal environment strain, as chassis to construct an SMX degradation pathway, obtaining a new bacteria for simultaneous degradation of SMX and removal of ammonia nitrogen. In doing this, we first identified and characterized four native promoters of P. denitrificans DYTN-1 with gradient strength to control the expression of the SMX degradation pathway. After degradation pathway expression level optimization and FMN reductase optimization, SMX degradation efficiency was significantly improved. The constructed P. d-pIAB4-P CS-sutR strain exhibited superior co-degradation of SMX and ammonia nitrogen contaminants with degradation rates of 44% and 71%, respectively. This study could pave the way for SMX degradation engineered strain design and evolution of environmental bioremediation. IMPORTANCE The abuse of sulfamethoxazole (SMX) had led to an increased accumulation in the environment, resulting in the disruption of the structure of microbial communities, further disrupting the bio-degradation process of other pollutants, such as ammonia nitrogen. To solve this challenge, we first identified and characterized four native promoters of Paracoccus denitrificans DYTN-1 with gradient strength to control the expression of the SMX degradation pathway. Then SMX degradation efficiency was significantly improved with degradation pathway expression level optimization and FMN reductase optimization. Finally, the superior nitrogen removal environment strain, P. denitrificans DYTN-1, obtained an SMX degradation function. This pioneering study of metabolic engineering to enhance the SMX degradation in microorganisms could pave the way for designing the engineered strains of SMX and nitrogen co-degradation and the environmental bioremediation.